Nanomaterial clusters as macroscopically small size-effects bodies. Part II (Archives of Mechanics - Test, 2000)
An isotropic elastic spherical size-effect solid body is proposed as a phenomenological model for the description of thermomechanical properties of macroscopically small nanomaterial spherical clusters subjected to a uniform pressure. Nanomaterial clusters being mechanically stable as well as those being mechanically stable of lower order are investigated. It is shown, among others, that the isothermal bulk modulus reveals the size effect due to the influence of surface tension of the cluster boundary solid surface.